Análise de populações de Sclerotinia sclerotiorum em cultura de feijoeiro através de marcadores SSR. - GOMES, Eriston Vieira (2009)
79 Sclerotinia sclerotiorum isolates were collected under central pivot irrigations sistems, from Brazilian fields, divided in 4 populations (S2, S3, A and M) and analyzed to determine the genetic variability among and between populations using molecular markers based on microsatelittes. 10 primers were used and the amplification products were separate in poliacrilamida gels and the bands were silver stained. A total of 102 different haplotypes were identified, and the amount of haplotypes varied from 6 to 18 for locus. The genotypic diversity ranged from 65% to 91%. Analyses based on genetic diversity and fixation indices which indicate the variability between populations was 28.79% (FST = 28793) and the variability among populations was 71.21%. The Jaccard similarity index indicated that the populations S2 and A is genetically closer. The population S3 presented a similarity index of 0.44 compared with the populations S2 and A. The population M, originated from several collection sites, was considered genetically more distant showing a index of 0.46 compared with the others populations . The high variability between and among populations can indicate that, besides the possible introduction of new genotypes in the analyzed fields, could be having clonal and sexual reproduction in isolated of S. sclerotiorum from Brazilian cerrado.